Laser land leveling in Indonesia, Philippines, Myanmar, Sri Lanka - CGIAR Research Program on Rice (2019)
In the Philippines, Sri Lanka, Myanmar, Thailand and Indonesia field demonstrations are being conducted for awareness generation and to collect data about cost and benefits. In Myanmar a local distributor for the laser equipment is being established in 2019. In Thailand and Myanmar laser leveling are included in government outreach.